REACTION-MECHANISMS OF POLYACRYLONITRILE ON THERMAL-TREATMENT - KIM, J; KIM, YC; AHN, W; KIM, CY (SOC PLASTICS ENG INC, 1993)
A high-temperature radical scavenger, 2,2-diphenyl-1-picryl hydrazyl (DPPH), has been used to study the reaction mechanisms of polyacrylonitrile (PAN) on thermal treatment. The effect of DPPH on the cyclization reaction of PAN in both air and nitrogen, investigated by differential scanning-calorimetry (DSC), helped to verify the proposed reaction mechanisms, i.e., the free radical and the ionic ones. For PAN homopolymer, the peak temperature of the reaction exotherm shifted to higher temperatures and the heat of reaction was decreased with increasing DPPH concentration. For PAN copolymer with methylacrylate and itaconic acid, however, the effects of DPPH on DSC thermograms were insignificant. The effects of DPPH suggest that the reaction of the nitrile groups proceeds by free radicals for the homopolymer while by ions for the copolymer. The activation energies for the thermal reactions of PAN in both air and nitrogen were also estimated by the dynamic DSC method, and they proved to be highly dependent on reaction mechanism, environment of thermal treatment, and DPPH concentration.
Keywords: PAN FIBERS; PYROLYSIS; POLYMERS; ACRYLONITRILE; STABILIZATION; COPOLYMERS